Treatment of large, massive irreparable rotator cuff tears - Maxim F. Lazko (Клиническая практика, 2020)
The rotator cuff is a complex anatomical and biomechanical structure which allows stabilization of the shoulder joint in the correct position and movements in it. The rotator cuff tears remain the most frequent injury as compared to those of other anatomical structures of the shoulder joint and reach the incidence of 21%, according to a number of authors. Such injuries are prone to inducing a fat replacement of muscle tissues in elderly patients against the background of degenerative changes in the structure of the rotator cuff. These injuries are hard-to-heal, and the incidence of relapses after the surgical treatment reaches 2090%, according to several authors. Based on the investigation of the postoperative treatment failures, alternative methods for the replacement, transfer or surgical repair of damaged tendons are adopted, but there is still no single approach and method in the treatment of this pathology. In this literature review, we have analyzed the data on the anatomical structure and biomechanics of the rotator cuff, the role of the rotator cuff damage in the dysfunction of the shoulder joint and possible methods for its recovery.